Using Latent Profile Analysis to Harness the Heterogeneity of Nonretained College Students. (February 2017) - Sulak, Tracey N.; Massey, Jennifer; Thomson, David
Universities struggle to raise retention rates among first-year students. Traditional analyses have not only focused on large-scale issues and addressed the needs of the majority but also done little to change overall retention numbers. The current study demonstrates the benefit of using a person-centered approach to retention research. Latent profile analysis was used to examine all nonretained, first-year students ( n = 515) from the 2011 cohort at a private, research-intensive university. The larger population of nonretained first-year students appeared to contain several smaller, subpopulations, and these smaller groups differed on key variables collected by the university. The differences in the subpopulations indicate a need for greater specificity in retention programming.